Teacher Training on Digital Media Utilization to Improve Learning Effectiveness in MIS Al-Afkari - Torkis Dalimunthe (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
The integration of digital media in teaching has become increasingly important in enhancing learning effectiveness and student engagement. However, many teachers, particularly in madrasah-based schools, face challenges in utilizing digital media due to limited digital literacy and lack of structured training. This community service program aimed to improve teachers’ competencies in using digital media to support effective learning at MIS Al-Afkari. The program employed a training-based and participatory approach involving teachers from various subject areas. The activities were conducted through needs assessment, workshops, demonstrations, guided practice, and evaluation sessions. The training focused on the development of digital learning materials, the integration of multimedia content into lesson planning, and the application of interactive teaching strategies. Data were collected through observations, review of teachers’ learning products, and feedback questionnaires, and analyzed descriptively. The results indicate that the training program positively impacted teachers’ knowledge, skills, and confidence in utilizing digital media for instructional purposes. Teachers demonstrated improved ability to design interactive learning materials and implement more student-centered teaching practices. Additionally, teachers reported increased student engagement and more effective learning interactions in the classroom. Despite challenges related to technological infrastructure and varying levels of digital literacy, the program proved effective in enhancing teaching quality. Overall, this community service initiative highlights the importance of continuous teacher training in digital media utilization to improve learning effectiveness and supports sustainable professional development in educational institutions.